Thermally activated delayed fluorescence and high-contrast mechanochromism of anthrone-based donor–acceptor systems - Sudhakar, Pagidi; Slawin, Alexandra; Zysman-Colman, Eli (Frontiers in Chemistry, 2023)
The development of materials that emit in the deep red to near-infrared region of the spectrum has attracted significant attention on account of their potential as optical sensing and imaging reagents in biology. We report herein the synthesis and optoelectronic characterization of four anthraquinone-based emitters T-tBuCz-AQ, T-MeOCz-AQ, C-tBuCz-AQ, and C-MeOCz-AQ, and two pyrazoloanthrone-based emitters tBuCz-PA and DMAC-PA. Depending on the donor, these compounds emit between 640-750 nm in the neat film, while the emission of the 10 wt% doped films in PMMA are blue-shifted to between 600-700 nm and have low photoluminescence quantum yields of between 2.6-6.6%. Of these compounds, T-tBuCz-AQ, T-MeOCz-AQ, and C-tBuCz-AQ exhibited thermally activated delayed fluorescence in 10 wt% doped films in PMMA, while the crystals of T-tBuCz-AQ also showed TADF. Compound tBuCz-PA showed highcontrast and reversible PL response upon mechanical grinding and hexane fuming.